Resources, production and structural dynamics - Baranzini, Mauro L.; Rotondi, Claudia; Scazzieri, Roberto (Cambridge University Press, 2015)
Economists since the First Industrial Revolution have been interested in the links between economic growth and resources, often pointing to resource scarcities as a hindrance to growth. Offering a counter perspective, this volume highlights the positive role that scarcities can play in inducing technical progress and economic growth. It outlines a structural framework for the political economy of scarcity and rents, and offers a novel way of organizing the evidence concerning the role of resources in industrial growth. This book proposes a major shift in the treatment of scarcity issues by focusing on bottlenecks and opportunities arising within the production system, and will appeal to economists and policy makers interested in the role of resources as triggers of structural change